Can virtual reality have a positive influence on student engagement? - Grewe, M.; Gie, L. (South African Journal of Higher Education, 2023)
Through the rapid development of virtual reality (VR), South African Higher Educational Institutions (HEIs) have shown interest in the potential VR has in teaching and learning practices. HEIs are further urged by the South African government to use cutting edge educational technology (edtech) tools to promote student engagement and limit the high dropout rates noticeable in HEIs. The researcher explored the perceived impact VR can have on student engagement. A qualitative research methodology was adopted for this study and the research instruments included open-ended questionnaires, semi-structured interviews, and a true experiment. Thirty-six participants took part in the study. The results of the study highlight a 23 per cent higher pass rate and a 180 per cent higher engagement level in students using VR as opposed to students studying via online distance learning. Two themes emerged from the results, namely: (1) the use of VR in teaching and learning, and (2) the influence VR has on student engagement levels. The results of this study further highlight that VR learning yields higher student engagement levels and as a result, students achieve higher marks. The significance of the study lies in the assistance it can offer higher educational institutions in their decision-making process of adopting VR into their teaching and learning processes.